Challenges in Management of Ovotesticular Differences in Sex Development in Resource-Limited Settings - Serwah Bonsu Asafo-Agyei; Emmanuel Ameyaw; Boateng Nimako; Michael Amoah (Case Reports in Endocrinology)
Differences in sex development (DSD) are congenital conditions in which the development of chromosomal, gonadal, or anatomical sex is atypical. Ovotesticular DSD is the rarest variant of DSD where both ovarian and testicular tissues co-exist in an individual. Ambiguous genitalia may be a glaring indicator of DSD, but multiple genital anomalies should also raise a suspicion of DSD. This is a case report of a 15-year-6-month-old boy who presented during infancy with multiple genital anomalies requiring surgery. The diagnosis of ovotesticular DSD was missed until later in adolescence when he presented with progressive bilateral breast enlargement. Work-up revealed a 46, XX karyotype and dysgenetic testes, but functional ovarian tissue. The patient wanted to consider switching to a female gender but was constrained by psychosocial factors. Maintenance of a masculine phenotype was done using testosterone injections due to the relatively high cost of testosterone patches. Conclusion. Multiple genital anomalies should raise the suspicion of DSD, and prompt referral to an endocrinologist should be done before urogenital surgery and gender assignment are carried out.